Perancangan dan Implementasi ERP (Enterprise Resource Planning) Modul Sales Pada PT Kanefusa Indonesia - eko prabowo; Kusnadi Suparman; Nika Rediyan; Marianus Bryan S; Irama Harefa (SOTVI - Society of Visual Informatics, 2022)
ERP (Enterprise Resource Planning) is a business process management software that allows companies to use integrated applications to support and facilitate the running of business operational activities in a company and is computerized. The company PT Kanefusa Indonesia is a company engaged in the manufacturing sector. This company is starting to develop and wants to switch to a computerized system, therefore an ERP system will be applied to the company PT Kanefusa Indonesian. The author will design and implement an ERP Sales module for the sales department as a means to convey information related to sales and delivery activities. The Open Source ERP used is Odoo. This Odoo Open Source ERP application is compatible with business processes with various efficiency features available. Then the feasibility of the program will be analyzed through a questionnaire form.